Tinjauan Hukum Islam Terhadap Praktek Bagi Hasil Tanaman Padi Pada Kalangan Petani Di Kemukiman Bambi - Mustajab, Muhammad; Aulia, Vivi (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to determine the form of practice for the production of muzara'ah rice crops carried out by farmers and the causes of muzara'ah practices and Islamic legal views on violations of muzara'ah practices that have been carried out by the people of Kemukiman Bambi, Peukan Baro District, Pidie Regency. In this thesis the author uses a descriptive method with data collection techniques through observation, interviews and documentation. The results of the study indicate that the form of violation of muzara'ah practices committed by farmers in Bambi Village, Peukan Baro District, is that farmers want to get more profits and are not in accordance with an agreement that has been agreed upon, where farmers feel that everything is done by themselves and all risks that occur while working on the fields are their own responsibility. The cause of the violation of muzara'ah practices carried out by farmers in the Bambi Village, Peukan Baro District, was caused by dishonesty from the farmers and because of the very high need factor and it was very detrimental to the land owner. The view of Islamic law on the violation of muzara'ah practices that have been carried out by the community in the Bambi Village, Peukan Baro District is not appropriate because the farmers or cultivators are dishonest, therefore it is expected that all parties are always in accordance with what has been taught by Islam. Therefore, farmers must always be honest with land owners regarding the agreed practice of the muzara'ah contract.